2018
DOI: 10.4103/ija.ija_549_17
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study comparing criteria-based discharge method with traditional time-based discharge method for discharging patients from post-anaesthesia care unit undergoing ambulatory or outpatient minor surgeries under general anaesthesia

Abstract: Background and Aims:Mostly, institutions in India have single post-anaesthesia care unit (PACU) which follows traditional time-based discharge (TBD) method. Recently, it has been classified into PACU Phase I and Phase II, and criteria-based discharge (CBD) method has been used. This study primarily compares CBD versus TBD methods in moving patients through PACU, and other non-clinical factors causing delay in shifting.Methods:One hundred patients, aged 18–65 years, American Society of Anesthesiologist's physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Traditionally, time based discharge method has been used to discharge patients from post-anesthesia care unit. Which varies from institution to institution, whereas modi ed Alderte,s score method standardizes and objecti es the discharge criteria across the institutions (13).Our study showed that only 73.3 % patients were meet the audit standard. This nding was low compared with the standard as well as with the other studies.…”
Section: Discussionmentioning
confidence: 77%
“…Traditionally, time based discharge method has been used to discharge patients from post-anesthesia care unit. Which varies from institution to institution, whereas modi ed Alderte,s score method standardizes and objecti es the discharge criteria across the institutions (13).Our study showed that only 73.3 % patients were meet the audit standard. This nding was low compared with the standard as well as with the other studies.…”
Section: Discussionmentioning
confidence: 77%
“…reported the successful use of the LMA Protector™ in three patients scheduled for elective laparoscopic cholecystectomy. [ 13 ] In their assessment, the LMA Protector™ possessed oropharyngeal leak pressures and maximum minute ventilation of ranges 27-31 cm H 2 O and 15.1-21.8 l/min, respectively. These are above the thresholds of 25 cm H 2 O for oropharyngeal leak pressure and 12 l/min for maximum minute ventilation considered to reflect adequate clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…At almost all PACUs (93.3%), the staff used predetermined discharge criteria. Recent studies have shown that the discharge criteria based on a predetermined physiological scoring system can reduce the length of stay in the PACU (Jain et al 2018, Street et al 2017, 2018 and is cost-effective (Street et al 2017). Furthermore, this method increases patient safety by identifying patients at a greater risk of adverse events, thereby decreasing the rate of clinical deterioration and cardiac events following discharge from the PACU (Nilsson et al 2020, Street et al 2017.…”
Section: Discussionmentioning
confidence: 99%